SKELETAL MUSCLE INSULIN SENSITIVITY AND DURATION OF TYPE 2 DIABETES MELLITUS - Ernst, Jacob Matthew (East Carolina University, 2012)
Type 2 Diabetes Mellitus (T2DM) resolution following Roux-en Y gastric bypass (RYGB) surgery is reduced in patients with longer duration of T2DM and preliminary data suggest this may be mechanistically linked to lower pre-RYGB insulin sensitivity. Insulin sensitivity is reduced in T2DM. Skeletal muscle accounts for 60-80% of insulin mediated glucose disposal. PURPOSE: It was hypothesized that insulin sensitivity would be lowest in T2DM patients with long-duration (LD; [greater than or equal to] 8 y) compared to short-duration (SD; < 8 y). METHODS: Insulin sensitivity (Si) and the acute response to glucose (AIRg) were measured following an insulin modified intravenous glucose tolerance test (IVGTT) using Minimal Model analysis in T2DM patients (N = 14). RESULTS: There was a significant (p = 0.010) difference in Si between short and long T2DM duration (LD: 0.47 ± 0.7; SD: 1.94 ± 0.96 min/mU/ml) and a significant correlation between Si and duration of T2DM (r = -0.70; p = 0.010). There was a significant difference in AIRg between groups. There was a significant correlation between HbA1c (an index of glycemic control) and Si (r = -0.76; p = 0.002), but not between HbA1c and AIRg (r = -0.36; p = 0.204). CONCLUSIONS: Insulin sensitivity is lower in T2DM patients with longer duration of T2DM. Clinically, poor glycemic control in long duration T2DM may be partially explained by reduced skeletal muscle insulin sensitivity.
Keywords: Kinesiology; Physiology; Diabetes; Duration; Sensitivity; Biology, Physiology; Diabetes--Research; Insulin; Musculoskeletal system; Gastric bypass